Hemostasis disorder as a reason of periodontitis in patients with diabetes mellitus - E. A. Shevchenko; T. E. Potemina; E. G. Ivanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
In diabetes mellitus II type hyperglycemia contributes to the development of endothelial dysfunction. It leads to hypercoagulation and severe microcirculation disorders, which are the cause of ischemia in periodontal tissues and the development of inflammatory processes. The aim of the study hemostasis indicators associated with endothelial dysfunction to study the etiology of periodontitis in patients with type II diabetes mellitus. Materials and methods. 46 people aged 50–80 years were examined. 20 patients planned hospitalized, with compensated type II diabetes mellitus without complications and other diseases and 26 healthy people were examined as a control group, comparable in age and sex to the patients with SDS. Blood was taken when patients were admitted to the hospital before the treatment. For all studied parameters, a multiple and pairwise comparison was carried out. Results. Considerable changes in endothelial function were found in patients with DFS. There was a significant increase in the concentration in blood serum of indicators such as d-dimers (10.5 times more compared with the control values), factor XIIa (8.4 times more), Willibrand factor (2 times more). The increase in the concentration of fibrinogen, INR and antiplasmin in the plasma of patients with DFS was also revealed. In addition, there was a significant decrease in antithrombin content by 17% compared to control values. Conclusions. The hemostatic system is involved in a wide variety of pathogenetic links in the inflammatory process in periodontal tissues. Due to endothelial disfunction and the damaging effect of hyperglycemia on the cell membranes, hemostasis is activated, so it leads to the thrombosis. This is the cause of severe microcirculation disorders, which further contribute to changes in the periodontal tissues and to the development of inflammatory processes in patients with type II diabetes mellitus.